Strength, body composition, and functional outcomes in the squat versus leg press exercises - Rossi, Fabricio E. [UNESP]; Schoenfeld, Brad J.; Ocetnik, Skyler [UNESP]; Young, Jonathan [UNESP]; Vigotsky, Andrew; Contreras, Bret; Krieger, James W.; Miller, Michael G.; Cholewa, Jason (Edizioni Minerva Medica, 2018)
BACKGROUND: The purpose of this study was to compare strength, body composition, and functional outcome measures following performance of the back squat, leg press, or a combination of the two exercises. METHODS: Subjects were pair-matched based on initial strength levels and then randomly assigned to 1 of 3 groups: a squat-only group (SQ) that solely performed squats for the lower body; a leg press-only group (LP) that solely performed leg presses for the lower body, or a combined squat and leg press group (SQ-LP) that performed both squats and leg presses for the lower body. All other RT variables were held constant. The study period lasted 10 weeks with subjects performing 2 lower body workouts per week comprising 6 sets per session at loads corresponding to 8-12 RM with 90- to 120-second rest intervals. RESULTS: Results showed that SQ had greater transfer to maximal squat strength compared to the leg press. Effect sizes favored SQ and SQ-LP versus LP with respect to countermovement jump while greater effect sizes for dynamic balance were noted for SQ-LP and LP compared to SQ, although no statistical differences were noted between conditions. CONCLUSIONS: These findings suggest that both free weights and machines can improve functional outcomes, and that the extent of transfer may be specific to the given task.
Keywords: Physical fitness; Resistance training; Exercise